2009
DOI: 10.5194/acp-9-7213-2009
|View full text |Cite
|
Sign up to set email alerts
|

One year of CNR-IMAA multi-wavelength Raman lidar measurements in coincidence with CALIPSO overpasses: Level 1 products comparison

Abstract: Abstract. At CNR-IMAA, an aerosol lidar system has operated since May 2000 in the framework of EARLINET (European Aerosol Research Lidar Network), the first lidar network for tropospheric aerosol study on a continental scale. High quality multi-wavelength measurements make this system a reference point for the validation of data products provided by CALIPSO (Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations), the first satellite-borne lidar specifically designed for aerosol and cloud study. Si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 32 publications
3
92
0
Order By: Relevance
“…Other studies have also found good agreement between CALIOP and ground-based lidar measurements (e.g., Mamouri et al, 2009;Mona et al, 2009).…”
Section: Satellite Observationsmentioning
confidence: 78%
“…Other studies have also found good agreement between CALIOP and ground-based lidar measurements (e.g., Mamouri et al, 2009;Mona et al, 2009).…”
Section: Satellite Observationsmentioning
confidence: 78%
“…Since the launch of CALIPSO, several studies have been conducted validating the CALIOP data products (Mona et al, 2009;Mamouri et al, 2009;Kim et al, 2008). Some promising results were also published by McGill et al (2007) qualitatively comparing measurements from CALIOP to the Cloud Profiling Lidar (CPL) deployed on the ER-2 aircraft.…”
Section: Introductionmentioning
confidence: 86%
“…In clear sky conditions, Mona et al (2009), found CALIOP to bias slightly low in the free troposphere and very low in the PBL (below 2.5 km). Pappalardo et al (2010) show similar results from comparisons between several EARLINET lidars and CALIOP with similar results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the following we compare the attenuated backscatter coefficient available from all the instruments, and different calibration techniques according to the availability of the raw signals. The attenuated backscatter coefficient β is calculated using the Raman lidar retrieval of extinction for the MUSA lidar is defined as (Mona et al, 2009):…”
Section: Comparison Of Lidar and Ceilometer Attenuated Backscatter Comentioning
confidence: 99%